The Nature Of Firm’s Internal Environment Capabilities And Competencies Dynamics Evaluation: Feasible Strategy Crafting Imperatives - John E. Chikwe; Chris Sam Biriowu (The American Journal of Management and Economics Innovations, 2020)
The study strategically evaluated the nature of firm’s internal environment capabilities and competencies dynamics that will ensure feasible strategy crafting. The understanding and analysis of the challenges posed in the internal environment helps strategists to make strategic decisions relating to the resources, capabilities and core competencies since they are non routine. In order to facilitate the development and effective usage of core competencies, managers/strategists are advised to have courage, self-confidence, integrity, the capacity to deal with uncertainty and complexity, and a willingness to hold people accountable for their work, as well as their being accountable themselves. This should be necessitated because the competitive advantage and firm’s performance are often strongly related to the resources firms hold and how they are managed. This is found to be so, since human beings are strategic critical resource that produces innovation, develops policies and strategies, and firm’s competitive advantage enhancement. The study further explored some related perspectives of valuable capabilities, personnel and organizational competencies, resources tangibility and intangibility, as well as competitive advantage sustainability criteria that will guide feasible strategy crafting. The study recommends amongst others, that organization managers should as a matter of necessity, monitor and evaluate the internal environment capabilities and competencies in order to have fit with that of external resources dynamics to enhance feasible strategy crafting.